Behavior of the transport and separation of lanthanum, yttrium and lutetium metal ions through a celluose fiber supported solid membrane - Gaikwad, Abaji G. (Macedonian Journal of Chemistry and Chemical Engineering, 2012)
A newly designed membrane cell was used to study the behavior of the transport and separation of lanthanum, yttrium and lutetium metal ions using a cellulose fiber supported solid membrane. The cellulose fiber membrane was prepared by the chemical modification of cellulose fiber using an esterification reaction with citric acid. Different experimental variables were investigated, such as time, membrane size, stirring of the source and receiving phases and the pH of the source phase. The use of different stripping agents in the receiving phase was explored, including nitric acid, hydrochloric acid, sodium nitrate, ammonium thiocyanate, D(2)EHPA, TBP, Aliquat-336, tartaric acid, EDTA and organic solvents. Pre-concentration of lanthanum, yttrium and lutetium metal ions from dilute solutions was carried out.
Keywords: binary mixture; cellulose fiber membrane; Citric acid; complexing reagent; Lanthanum; lutetium; metal ions; Separation; transport studies; yttrium